2015
DOI: 10.1364/boe.6.004212
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional printed optical phantoms with customized absorption and scattering properties

Abstract: Three-dimensional (3D) printing offers the promise of fabricating optical phantoms with arbitrary geometry, but commercially available thermoplastics provide only a small range of physiologically relevant absorption (µa) and reduced scattering (µs`) values. Here we demonstrate customizable acrylonitrile butadiene styrene (ABS) filaments for dual extrusion 3D printing of tissue mimicking optical phantoms. µa and µs` values were adjusted by incorporating nigrosin and titanium dioxide (TiO2) in the filament extru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…The exact optical and autofluorescence properties of the printed material are not known, but we and others have observed that these approximate that of biological tissue at near-infrared wavelengths. 12 The phantom was 6 mm in diameter, 20 mm in length, with a 0.8-mm clear cylindrical channel centered 0.75 mm from the surface. We threaded a strand of 250-μm internal diameter Tygon tubing (TGY-010-C, Small Parts, Inc., Seattle, Washington) through the channel and connected it to a syringe on a microsyringe pump (70-2209, Harvard Apparatus, Holliston, Massachusetts) configured to produce a flow speed of 5 mm∕s (15 μL∕ min).…”
Section: Validation In Optical Phantoms In Vitromentioning
confidence: 99%
“…The exact optical and autofluorescence properties of the printed material are not known, but we and others have observed that these approximate that of biological tissue at near-infrared wavelengths. 12 The phantom was 6 mm in diameter, 20 mm in length, with a 0.8-mm clear cylindrical channel centered 0.75 mm from the surface. We threaded a strand of 250-μm internal diameter Tygon tubing (TGY-010-C, Small Parts, Inc., Seattle, Washington) through the channel and connected it to a syringe on a microsyringe pump (70-2209, Harvard Apparatus, Holliston, Massachusetts) configured to produce a flow speed of 5 mm∕s (15 μL∕ min).…”
Section: Validation In Optical Phantoms In Vitromentioning
confidence: 99%
“…The rise in popularity and capability of rapid prototyping tools, such as 3D printers and computer controlled milling machines, has allowed for a new generation of physical mouse phantoms with intricate features that closely mimic the animals they represent. Multiple mouse phantoms have been created using 3D printing, but they are often homogenous (22) and any heterogeneities that can be created are limited to variations in optical response (23, 24). Bache et al .…”
Section: Introductionmentioning
confidence: 99%
“…The rise in popularity and capability of rapid prototyping tools, such as 3D printers and computer controlled milling machines, has allowed for a new generation of physical mouse phantoms with intricate features that closely mimic the animals they represent. Multiple mouse phantoms have been created using 3D printing, but they are often homogenous (22) and any heterogeneities that can be created are limited to variations in optical response (23,24). Bache et al employed 3D printing to produce molds for optical dosimeters, which had the same anatomical shape as small sections of a mouse, but those dosimeters also lacked structures to mimic bones and other regions of density inhomogeneity (25).…”
Section: Introductionmentioning
confidence: 99%